Comparison of the clinical effectiveness of Bone Morphogenic Protein (BMP) -2 and -7 in the adjunct treatment of lower limb nonunions - Haubruck, Patrick; Tanner, Michael Christopher; Vlachopoulos, Wasilios; Hagelskamp, Saskia; Miska, Matthias; Ober, Julian; Fischer, Christian; Schmidmaier, Gerhard (Orthopaedics & traumatology, 2018)
Background - Substantial evidence exists demonstrating the individual effectiveness of both rhBMP-2 and -7 in the treatment of nonunions, data comparing the clinical effectiveness of adjunct rhBMP-2 and -7 remains scarce. Therefore, we examined our large single-center case series to compare the clinical effectiveness of both rhBMP-2 and -7 in non-union therapy aiming to answer: - Does a certain type of BMP have an advantageous effect on radiological outcome of applied lower limb non-union therapy? - Does application of a certain type of BMP have an advantageous effect on radiological outcome of infected lower limb nonunions? - Are there any additional risk factors associated with inferior outcome in context with an adjunct BMP treatment? - Hypothesis - Both BMPs have the same effect on the radiological outcome of surgically treated lower limb nonunions. - Patients and methods - Single-center retrospective database analysis of a case series of patients with lower limb long bone nonunions receiving either a one- or two-stage (Masquelet-) procedure based on the “diamond concept” with application of rhBMP-2 or -7. The “diamond concept” summarizes core factors that need to be present to achieve bone healing. In particular, these factors relate to the optimization of the mechanical (stability) and biological environment (sufficient osteogenic and angiogenic cells, osteoconductive scaffolds and growth factors). All medical data from patients that received surgical treatment between 01/01/2010 and 31/12/2016 were assessed. In total, 356 patients were treated with BMPs and 156 patients 18 years or older with non-union of their tibia or femur having a follow-up of at least 1 year were included. Consolidation in context with type of rhBMP was compared and the influence of relevant risk factors assessed. - Results - Consolidation rate was significantly higher in patients treated with rhBMP-2 (rhBMP-2: 42/46 (91%) vs. rhBMP-7: 64/110 (58%); p<0.001). In particular, application of rhBMP-2 increased the likelihood of consolidation for tibial nonunions (OR 32.744; 95%CI: 2.909-368.544; p=0.005) and when used in two-stage therapy (OR 12.095; 95% CI: 2.744-53.314; p=0.001). Furthermore, regression modeling revealed a higher correlation between application of rhBMP-2 and osseous consolidation in infected nonunions (OR 61.062; 95% CI: 2.208-1688.475; p=0.015) than in aseptic nonunions (OR 4.787; 95% CI: 1.321-17.351; p=0.017). Risk factors negatively influencing the outcome of non-union treatment in context with rhBMPs were identified as active smoking (OR 0.357; 95% CI: 0.138-0.927; p=0.024), atrophic nonunion (OR 0.23; 95% CI: 0.061-0.869; p=0.030), higher BMI (OR 0.919; 95% CI: 0.846-0.998; p=0.046) and a larger defect size (OR 0.877; 95% CI: 0.784-0.98; p=0.021). - Discussion - Patients who received rhBMP-2 for the treatment of tibial nonunions and as part of the two-stage treatment had a significantly higher rate of healing compared to patients treated with rhBMP-7 regardless of infection. - Level of evidence - III, retrospective case-control study.
Gesehen am 17.10.2019